Is Irisin a Phenotypic Parameter in Over-Weight Women with Polycystic Ovary Syndrome? (Medico Legal Update, 2020)
Polycystic ovary syndrome (PCOS) is the most public hormonal chaos and the causesthe infertility inthe women of reproductive age, offering a varied set of clinical parameters.Irisin had assumed to have aduty in metabolic conditions and PCOS. However, the correlation between irisin and metabolic conditionsin PCOS is not clear.The purpose of this control cases study was to evaluate the plasma levels of Irisinin women with overweight PCOS and its correlations with other phenotypes parameters of PCOS. Thestudy involved 90 PCOS women and 40 control healthy women. The PCOS womenwere diagnostic byBMI as overweight. Statistical analysis was performed by using by the SAS (2012) program1.Chiefresultsmeasure was to determinethe plasma Irisin levels in overweight cases. In addition, some phenotypic andanthropometric parametersincluding BMI, lipid profile, sex hormones, FBG, Insulin, and HOMA-IRhadmeasured in groups of the study. Results offasting Irisin levels showed significantly elevated differences inoverweight PCOS women as compared to the levels in overweight control women(P